Optimizing Administrative Efficiency: The Impact of ICT Adoption and Change Management in Educational Institutions - Hamza Abubakar Usman; Hameed Olalekan Bolaji (JUMPA : Jurnal Manajemen Pendidikan, 2023)
This study focuses on analyzing the impact of the limitations of Information and Communication Technology (ICT) infrastructure and resistance to changes to administrative efficiency at the Nigerian Army College of Education (NACOED), Sobi, Ilorin. The main objective of this study is to understand how these factors affect the performance of the institution and identify solutions that can improve operational efficiency. This study uses a qualitative approach with a case study method, where data is collected through in-depth interviews, participatory observations, and documentation analysis. The data analysis technique used is the Miles and Huberman analysis model, which involves data reduction, data presentation, and conclusion drawing and verification. The results show that the limitations of ICT infrastructure and resistance to change significantly hinder administrative efficiency, with major problems related to low hardware specifications, unstable internet connections, and lack of training and technical support. The implications of this study emphasize the need for increased investment in ICT infrastructure and continuous training, as well as the development of effective change management strategies to overcome resistance to new technologies. This research makes a significant contribution to the development of educational management literature, especially in the context of military education